EFL learners’ beliefs about language learning along gender, further education in language institutes & different proficiency levels - Nahavandi, Naemeh; Mukundan, Jayakaran (Australian International Academic Centre, 2014)
The aim of the present study was to understand the beliefs of Iranian EFL learners’ about language learning. This study was an attempt to understand if there was any relationship between gender, proficiency level and further education in language institutes on beliefs about language learning. Accordingly, 369 EFL engineering students studying in Azad University of Tabriz, Iran were selected based on random sampling. Data were collected using two questionnaires: a demographical questionnaire, and the Beliefs about Language Learning Inventory (BALLI). Data were analyzed using ANOVA, LSD & t-test. The results of the study showed that the highest mean average among the five components of beliefs about language learning was nature of language learning (M=3.91), followed by Foreign Language Aptitude (M=3.85), Difficulty of Language Learning (M=3.42), Learning and Communication Strategies (M=3.35) and Motivation and Expectations (M=3.25). The findings showed that there was a significant difference between learners’ beliefs, gender and further education in language institutes. However, there was not any significant difference between learners’ beliefs and their proficiency level. The study concluded with some pedagogical implications.